Granzyme A Contributes to Inflammatory Arthritis in Mice Through Stimulation of Osteoclastogenesis. Issue 2 (28th January 2017) - Santiago, Llipsy; Menaa, Cheikh; Arias, Maykel; Martin, Praxedis; Jaime‐Sánchez, Paula; Metkar, Sunil; Comas, Laura; Erill, Nadina; Gonzalez‐Rumayor, Victor; Esser, Erica; Galvez, Eva M.; Raja, Sri; et al.
Abstract : Objective: Granzyme A (GzmA) levels are elevated in the plasma and synovium of patients with rheumatoid arthritis (RA), suggesting involvement of this protease in the pathogenesis of the disease. GzmA contributes to sepsis by regulating the production of proinflammatory cytokines. The purpose of this study was to evaluate the contribution of GzmA to the pathogenesis of RA in vivo and to examine the possibility that GzmA acting via tumor necrosis factor (TNF) stimulates osteoclastogenesis. Methods: Inflammatory arthritis induced by type II collagen was evaluated in wild‐type, GzmA‐deficient, and perforin‐deficient mice. The osteoclastogenic potential of GzmA was examined in vitro using bone marrow cells and colony‐forming unit–granulocyte–macrophage (CFU‐GM) cells and in vivo using GzmA‐deficient mice. Results: Gene deletion of GzmA attenuated collagen‐induced arthritis, including serum levels of proinflammatory cytokines, joint damage, and bone erosion in affected mice, suggesting that osteoclast activity is reduced in the absence of GzmA. Accordingly, GzmA‐treated bone marrow cells produced multinucleated cells that fulfilled the criteria for mature osteoclasts: tartrate‐resistant acid phosphatase (TRAP) activity, β integrin expression, calcitonin receptor expression, and resorptive activity on dentin slices. GzmA appeared to act without accessory cells, and its activity was not affected by osteoprotegerin, suggesting a minor contribution of RANKL. It also induced the expression and secretion of TNF. Neutralization of TNF or stimulation of CFU‐GM cells from TNF –/– mice prevented GzmA‐induced osteoclastogenesis. GzmA‐deficient mice had reduced osteoclastogenesis in vivo (fewer calcitonin receptor–positive multinucleated cells and fewer transcripts for cathepsin K, matrix metalloproteinase 9, and TRAP in joints) and reduced serum levels of C‐terminal telopeptide of type I collagen. Conclusion: GzmA contributes to the joint destruction of RA partly by promoting osteoclast differentiation.